Pathology and Pathobiology of Pulmonary Hypertension - Guignabert, Christophe; Dorfmüller, Peter (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary hypertension (PH) is a hemodynamic state defined by a mean pulmonary artery pressure ≥ 25 mm Hg during resting right heart catheterization. PH can result from precapillary (arterial) or postcapillary (venous) pathophysiological mechanisms. Interestingly, recent PH pathology has shown that pulmonary arterial or pulmonary venous remodelling are rarely independent phenomena, but frequently occur in combined fashion in lungs from patients suffering from different forms of PH, including pulmonary arterial hypertension (PAH). In PAH, it is now becoming clear that aberrant signals present in vessel wall microenvironment, which is largely orchestrated by dysfunctional pulmonary endothelial cells, are key contributors of the pulmonary vascular remodeling process, fostering proliferation, and survival and migration of resident pulmonary vascular cells such as smooth muscle cells, myofibroblasts, and pericytes. In addition, both genetic and environmental factors are also critical in the development of pulmonary vascular inflammation and chronic impairment of the pulmonary endothelium. This article outlines the current understanding of this disease from the point of view of pathology and pathobiology.
Keywords: pulmonary arterial hypertension; pulmonary vascular remodeling; endothelial dysfunction; inflammation; BMPR2